Systematic Review of the Literature: STEM Approaches in Learning to Improve Students' Argumentative Skills - Irnawati; Joko Waluyo; Indrawati; Pramudya Dwi Aristya Putra (Universitas Negeri Yogyakarta, 2026)
Scientific argumentation skills are essential competencies in 21st-century learning, which not only reflect students' critical and analytical thinking abilities, but also become the foundation for evidence-based decision-making. In the context of science learning, the integration of STEM approaches is believed to be able to strengthen students' ability to build and evaluate scientific arguments in more depth. This study aims to conduct a systematic literature review (SLR) on various STEM-based learning media and approaches used to improve students' argumentation skills. The review process was carried out by following the PRISMA 2020 protocol, including searching articles from reputable databases such as Scopus, SpringerLink, DOAJ, and Google Scholar. The inclusion criteria include articles published between 2015 to 2025, indexed by scopus Q1-Q4, explicitly mentioning argumentation skills, and being in the context of STEM education. Out of a total of 277 articles identified, 40 articles were selected for further analysis. The results of the study revealed that approaches such as argument-driven inquiry (ADI), project-based learning (PjBL), socioscientific issues (SSI), and engineering design process (EDP), have consistently proven to be effective in improving the quality of students' arguments. Learning media such as digital scaffolding, interactive simulations, argumentative worksheets, and argument mapping are widely used to support the critical thinking process and argument structuring. In addition, real-issue based learning and experimental activities show a positive impact on students' ability to structure claims, reasons, and evidence in a structured manner. This study makes an important contribution in directing the development of STEM learning designs that explicitly support the strengthening of scientific argumentation skills. The practical implications of this study include the need for teacher training, the integration of argumentation rubrics in assessments, as well as the development of adaptive digital learning media.